2020
DOI: 10.3389/fphar.2020.00263
|View full text |Cite
|
Sign up to set email alerts
|

Fitter Mitochondria Are Associated With Radioresistance in Human Head and Neck SQD9 Cancer Cells

Abstract: The clinical management of head and neck squamous cell carcinoma (HNSCC) commonly involves chemoradiotherapy, but recurrences often occur that are associated with radioresistance. Using human SQD9 laryngeal squamous cell carcinoma cancer cells as a model, we aimed to identify metabolic changes associated with acquired radioresistance. In a top-down approach, matched radiosensitive and radioresistant SQD9 cells were generated and metabolically compared, focusing on glycolysis, oxidative phosphorylation (OXPHOS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…showed that surviving cells from oncogene ablation in pancreatic cancer were reliant on OXPHOS and responsible for tumour relapse, while inhibition of OXPHOS decreased mitochondrial respiration and the ability of the surviving cells to form spheres affecting their survival [112] . Acquired radioresistance was also associated with a shift from a glycolytic to a more oxidative metabolism and to an increased number of mitochondria with a higher mtDNA content [113] .…”
Section: Role Of Metabolism In Radioresistancementioning
confidence: 98%
See 1 more Smart Citation
“…showed that surviving cells from oncogene ablation in pancreatic cancer were reliant on OXPHOS and responsible for tumour relapse, while inhibition of OXPHOS decreased mitochondrial respiration and the ability of the surviving cells to form spheres affecting their survival [112] . Acquired radioresistance was also associated with a shift from a glycolytic to a more oxidative metabolism and to an increased number of mitochondria with a higher mtDNA content [113] .…”
Section: Role Of Metabolism In Radioresistancementioning
confidence: 98%
“… Breast Increased PGC1α [110] Viale, A. et al Pancreatic Increased expression of OXPHOS genes [112] Grasso, D. et al. Head and neck cancer Increased OXPHOS metabolism [113] …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, mitophagy appears to have a dual role in cancer treatment resistance, as both its inhibition (in colorectal CSCs) and induction (in preclinical AML models) increased the sensitivity to chemotherapeutic drugs, such as doxorubicin [271]. Mitophagy could also participate in the radioresistance of head and neck cancer cells to γ rays [272].…”
Section: Mitophagy and Mitochondrial Transfermentioning
confidence: 99%
“…This suggests that tumors are able to use the mitochondrial metabolism as a substitute metabolic system for glycolysis, when they are in a high metabolic need. Therefore, this phenomenon can contribute to growth, metastatic formation and a radiation resistance phenotype (190)(191)(192). Besides the signaling-pathway-mediated and radiation-induced metabolic shift of the tumor cells, also the metabolic rewiring of the TME and CSC population can play an important role in treatment response.…”
Section: Metabolic Rewiring Upon Radiation Of Tumorsmentioning
confidence: 99%